Exportações de flores e plantas ornamentais brasileiras de 1996 a 2007: uma análise estatística da demanda - Garcia, Ricardo Sérgio Milfont (2009)
Brazilian flowers have increasingly attracted the interest of consumers in other countries in the international market. This dissertation presents a brief history of the flowers in Brazil, emphasizing the importance of marketing and socio-economic success that the foreign trade of floriculture products has brought to Brazil. Statistical analysis of the demand is made through a multiple regression model with the inclusion of seasonal dummies. In the first modeling the foreign income is represented by GDP and in the Netherlands, the U.S.GDP. Netherlands and United States are the two biggest importers of Brazilian products in the period studied. Thus, through the presentation and use of official statistics provided by the Ministry of Development Industry and Foreign Trade, there is the annual growth of export values and observes that the demand for these products is elastic to changes in income and inelastic to changes price, indicating that the species exported are few or no close substitute in competitor countries. These results may contribute to discussions based on the development and improvement of the performance of Brazilian exports of this product, and protect marketing actions towards the sector.